KEWENANGAN DEKONSENTRASI KEPALA DAERAH DALAM PENYELENGGARAAN PENGELOLAAN KEUANGAN DAERAH - Ismail, Nurwita (Universitas Gorontalo, 2019)
ABSTRACTDekonsentrasi Authority of the head of the region in implementing the financial management of this Research Area focuses on these problems. Using research methods normative legal science by using qualitative data analysis, comprehensive, and complete. Sebingga it was found that the results of research, organization of dekonsentrasi committed by the local government in line with the Undang-undnag Number 33 Year 2014 about equalization kuangan Central Government and local governments should It is a comprehensive system. Financial equalization is carried out in line with the governmental affairs division between the Government and the Government of the region, which is in the system settings not only covers aspects of revenue areas, but also aspects of the management and accountability. In line with that, then surrender the authority of the Government, pelimpahan the authority of Government, and the assignment from the Government in the framework of the Organization of the principle of decentralization, dekonsentrasi, and pembantuan should also be followed with the settings funding and utilization of the national resources efficiently and effectively.